2012
DOI: 10.3945/jn.111.142315
|View full text |Cite
|
Sign up to set email alerts
|

Whole Grain Compared with Refined Wheat Decreases the Percentage of Body Fat Following a 12-Week, Energy-Restricted Dietary Intervention in Postmenopausal Women

Abstract: Observational studies show inverse associations between intake of whole grain and adiposity and cardiovascular risk; however, only a few dietary intervention trials have investigated the effect of whole-grain consumption on health outcomes. We studied the effect of replacing refined wheat (RW) with whole-grain wheat (WW) for 12 wk on body weight and composition after a 2-wk run-in period of consumption of RW-containing food intake. In this open-label randomized trial, 79 overweight or obese postmenopausal wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
159
3
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(174 citation statements)
references
References 43 publications
10
159
3
2
Order By: Relevance
“…In this context, a decrease in BMI associated with more frequent consumption of wholegrain cereals (wholegrain rice and noodles, whole grains, and oat meal), fruits and vegetables, which was documented in our study, confirmed beneficial effect of these products with regards to the maintenance of due body weight. These findings are consistent with the results of a Danish study which revealed that wholegrain products play a role in the reduction of adipose tissue in postmenopausal women [18]. This is also important for gynecological practice as excess body weight represents one of main modifiable risk factors of breast and endometrial cancer [8].…”
Section: H -High M -Moderate or L -Low Level Of Self-efficacy (Gsessupporting
confidence: 82%
See 2 more Smart Citations
“…In this context, a decrease in BMI associated with more frequent consumption of wholegrain cereals (wholegrain rice and noodles, whole grains, and oat meal), fruits and vegetables, which was documented in our study, confirmed beneficial effect of these products with regards to the maintenance of due body weight. These findings are consistent with the results of a Danish study which revealed that wholegrain products play a role in the reduction of adipose tissue in postmenopausal women [18]. This is also important for gynecological practice as excess body weight represents one of main modifiable risk factors of breast and endometrial cancer [8].…”
Section: H -High M -Moderate or L -Low Level Of Self-efficacy (Gsessupporting
confidence: 82%
“…The cardioprotective role of wholegrain cereals, associated with normalization of the lipid profile of blood, was also confirmed in a study of Danish postmenopausal women [18]. Furthermore, the preference of cereals, fruits and vegetables among menopausal women reflects the influence of these products on body weight.…”
Section: H -High M -Moderate or L -Low Level Of Self-efficacy (Gsesmentioning
confidence: 65%
See 1 more Smart Citation
“…The sample size for the wholegrain protocol was estimated based on an expected difference in HOMA-IR between the wholegrain and the control periods of 0.25 with a weighted standard deviation of 0.6. The expected difference was based on an average difference of 0.26 among three difference studies [22,25,39]. The weighted standard deviation of 0.6 was based on unpublished data on within-group variation of 0.52 and 0.72 in refined grain and WG groups, respectively, from the study Kristensen et al 2012.…”
Section: Statistical Considerations Sample Size Estimationmentioning
confidence: 99%
“…A recent study of ten healthy individuals consuming a gluten-free diet for one month observed alterations in GM composition and lowered immune response [19]. Wholegrain consumption has been associated with a decreased risk of T2D and CVD in prospective studies [20,21] and has been suggested to beneficially influence glucose metabolism [22], adiposity [23,24], and blood lipids [25,26]. Wholegrains have prebiotic effects, due to the high content of dietary fibers [27], which by microbial fermentation lead to production of short-chain fatty acids (SCFA) [28].…”
Section: Introductionmentioning
confidence: 99%